Effects of Autonomous Vehicles on the Signalized Intersections’ Performance - Noaman, Mahmoud Atef (2021)
A Master of Science thesis in Civil Engineering by Mahmoud Atef Noaman entitled, “Effects of Autonomous Vehicles on the Signalized Intersections’ Performance”, submitted in July 2021. Thesis advisor is Dr. Akmal Abdelfatah. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).